IMPLEMENTASI CLUSTER SERVER BERBASIS LINUX SEBAGAI LEARNING MANAGEMENT SYSTEM (LMS) DI SMK MUHAMMADIYAH 2 PEKANBARU - Efendi, Yoyon; Lismanda, Hendra; Haryono, Dwi (Rang Teknik Journal, 2019)
Abstract Learning systems need help to support progress in the field of education. Problems that exist in Muhammadiyah 2 Pekanbaru Vocational School have not yet implemented a Learning Management System (LMS) system that has an impact on students and teachers, compilation teachers cannot discuss learning jams certainly greatly affect students, teachers who are unable to attend specifically at teaching hours. Learning methods by implementing Learning Management Systems that will run on the Ubuntu Server 16.04 LTS Linux operating system. The system contains features such as Moodle, Big BlueButton, and Video Confrence needed in the teaching and learning process. By using the Learning Management System the teacher can manage classes and exchange information with students. Using labor can use learning and video conferencing management systems to keep discussing and providing learning material to students when attending is present at the time of learning using the internet. Keywords: LMS, Server Cluster, Moodle, Big bluebutton, Muhammadiyah 2 Vocational School Pekanbaru AbstrakSistem pembelajaran membutuhkan suatu inovasi guna untuk mendukung kemajuan dibidang pendidikan. Masalah yang terdapat pada SMK Muhammadiyah 2 Pekanbaru belum diterapkan sistem Learning Management System (LMS) hal tersebut berdampak pada siswa dan guru, ketika guru tidak bisa menghadiri jam pembelajran tentu sangat berdampak pada siswa, terutama guru yang berhalangan hadir pada jam mengajar. Metode pembelajaran dengan menerapkan Learning Management System yang akan berjalan pada sistem operasi Linux Ubuntu Server 16.04 LTS. Sistem berisi fitur-fitur antara lain seperti Moodle, Big BlueButton, dan Video Confrence yang dibutuhkan dalam proses belajar mengajar. Dengan menggunakan Learning Management System guru dapat mengelola kelas dan bertukar informasi dengan siswa. Sehingga tenaga kerja dapat menggunakan learning management system dan video confrence untuk tetap mengawasi dan memberi materi pembelajaran kepada siswa/siswi pada saat berhalanagan hadir diwaktu pembelajaran dengan memanfaatkan internet. Kata kunci: LMS,Cluster server, Moodle, Big bluebutton, SMK Muhammadiyah 2 Pekanbaru